1979
DOI: 10.1017/s0021859600086081
|View full text |Cite
|
Sign up to set email alerts
|

Use of water by six grass species. 2. Root distribution and use of soil water

Abstract: The use of soil water by six grasses (perennial ryegrass, cocksfoot, timothy, rough stalked meadow grass (RSMG), tall fescue and Italian ryegrass) was measured over 2 years. The swards were cut either at 3-week (C 3 ) or 6-week (C 8 ) intervals. In both years the maximum soil water deficit attained under C 6 was greater than under C 3 . Following several of the cuts from C 6 there was a marked, although temporary, reduction in the rate of water uptake.An extended dry period in the second harvest year revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…While the roots of the granite A. millefolium ecotype and the annual grasses V. microstachys and B. madritensis were restricted to compost amended layers, the root distribution of the serpentine A. millefolium ecotype and the perennial grasses B. laevipes and E. elymoides was not restricted. Distribution of soil resources including nutrients (Robinson, 1994) and water (Garwood et al, 1979), and soil physical properties including spatial textural differences and rocks which present obstacles to rooting (Weaver and Darland, 1949), are known to have a substantial influence on plant root distribution. Classic root mapping studies of numerous grass species native to the US have demonstrated that most perennial, tillering bunch grasses have a relatively even horizontal distribution of roots throughout the soil profile with a steady vertical decline in root biomass with increasing soil depth (Weaver and Darland, 1949).…”
Section: Discussionmentioning
confidence: 99%
“…While the roots of the granite A. millefolium ecotype and the annual grasses V. microstachys and B. madritensis were restricted to compost amended layers, the root distribution of the serpentine A. millefolium ecotype and the perennial grasses B. laevipes and E. elymoides was not restricted. Distribution of soil resources including nutrients (Robinson, 1994) and water (Garwood et al, 1979), and soil physical properties including spatial textural differences and rocks which present obstacles to rooting (Weaver and Darland, 1949), are known to have a substantial influence on plant root distribution. Classic root mapping studies of numerous grass species native to the US have demonstrated that most perennial, tillering bunch grasses have a relatively even horizontal distribution of roots throughout the soil profile with a steady vertical decline in root biomass with increasing soil depth (Weaver and Darland, 1949).…”
Section: Discussionmentioning
confidence: 99%
“…In phalaris, the early onset and high level of senescence of herbage were observed to reduce transpiration (McWilliam 1968) while the development of an extensive root system and/or superior hydraulic conductance to maximise soil water uptake was noted as being important for ongoing production under drying conditions in tall fescue (Garwood and Sinclair 1979). Dehydration-avoiding plants are able to survive extended dry spells but can only do so if able to maintain high tissue water status.…”
Section: Dehydration Avoidance/delay and Rooting System Improvementmentioning
confidence: 99%
“…Thinopyron and Bromus continue to be cultivated while several other genera remain under evaluation. Apart from their adaptability, part of the popularity of the main four introduced perennial grasses would appear to be their deep root system, relative to annuals (Garwood & Sinclair 1979) which helps to prolong the period of active growth by utilising subsoil moisture (e.g., Donald 1970), their herbage and seed yield potentials, their nutritive value, and ease of establishment.…”
Section: Introductionmentioning
confidence: 99%